High-Entropy Alloys Fundamentals and Applications - Gao, Michael C.; Yeh, Jien-Wei.; Liaw, Peter K.; Zhang, Yong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a systematic and comprehensive description of high-entropy alloys (HEAs). The authors summarize key properties of HEAs from the perspective of both fundamental understanding and applications, which are supported by in-depth analyses. The book also contains computational modeling in tackling HEAs, which help elucidate the formation mechanisms and properties of HEAs from various length and time scales.
Overview of High-Entropy Alloys -- Phase Formation Rules -- Physical Metallurgy -- Advanced Characterization Techniques -- Fabrication Routes -- Mechanical Properties of High-Entropy Alloys -- Functional Properties -- Prediction of Structure and Phase Transformations -- Applications of Coherent Potential Approximation to HEAs -- Applications of Special Quasi-random Structures to High-Entropy Alloys -- Design of High-Entropy Alloys -- CALPHAD Modelling of High-Entropy Alloys -- High-Entropy Metallic Glasses -- High-Entropy Coatings -- Potential Applications and Prospects.
Keywords: Materials -- Analysis; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Nanoscience; Mechanics, Applied; Solids; Characterization and Analytical Technique; Engineering Thermodynamics, Heat and Mass Transfer; Nanophysics; Solid Mechanics